L'énigme du masochisme - André, Jacques (Petite bibliothèque de psychanalyse, 2001)
Introduction: Fundamental issues in sexual deviance / D. Richard Laws and William O'Donohue * Exhibitionism: Psychopathology and theory / William D. Murphy* Exhibitionism: Assessment and treatment / Barry M. Maletzky* Fetishism: Psychopathology and theory / Fiona L. Mason* Fetishism: Assessment and treatment / John Junginger* Frotteurism: The theory of courtship disorder / Kurt Freund, Michael C. Seto and Michael Kuban* Frotteurism: Assessment and treatment / Richard B. Krueger and Meg S. Kaplan* Pedophilia: Psychopathology and theory / W. L. Marshall* Pedophilia: Assessment and treatment / Howard E. Barbaree and Michael C. Seto* Sexual sadism: Psychopathology and theory / Stephen J. Hucker* Sexual sadism: Assessment and treatment / Clive R. Hollin* Sexual masochism: Deviance without pathology / Roy F. Baumeister and Jennifer L. Butler* Sexual masochism: Assessment and treatment / David Thornton and Ruth Mann* Transvestic fetishism: Psychopathology and theory / Kenneth J. Zucker and Ray Blanchard* Transvestic fetishism: Assessment and treatment / Gwen Adshead* Voyeurism: Psychopathology and theory / Meg S. Kaplan and Richard B. Krueger* Voyeurism: Assessment and treatment / R. Karl Hanson and Andrew J. R. Harris* Rape: Psychopathology and theory / Stephen M. Hudson and Tony Ward* Rape: Assessment and treatment / Tony Ward, Julie McCormack, Stephen M. Hudson and Devon Polaschek* Paraphilia not otherwise specified: Psychopathology and theory / Joel S. Milner and Cynthia A. Dopke* Paraphilia not otherwise specified: Assessment and treatment / Paul A. Schewe* Medical models of sexual deviance / Don Grubin and Debbie Mason* Medical interventions in sexual deviance / John Bradford* Sexual deviance in females / John A. Hunter and Ruth MathewsFuture directions / Stephen M. Hudson and Tony Ward